2020
DOI: 10.20885/ajim.vol2.iss2.art2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social media marketing and religiosity on perceived value and student’s decision in choosing non-religious program at Islamic higher education

Abstract: This study aims to examine the effect of social media marketing and religiosity on perceived value and student's decision in choosing non-religious programs at Islamic Higher Education.Methodology: This study conducted an online survey on 158 respondents who are studying non-religious programs in three Islamic Higher Education institutions in Indonesia, namely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Jika dilihat dari hasil Tstatistics dan P value nya, dari total 9 hipotesis yang diuji, 4 diantaranya tidak menunjukkan hubungan yang signifikan dan tidak menunjukkan hasil yang sejalan dengan penelitian terdahulu. 19,20 Studi lainnya oleh Kaur et al (2021) menunjukkan adanya pengaruh yang positif dan signifikan dari epistemic value terhadap purchase intention, maka dapat disimpulkan bahwa dengan pemasaran produk di media sosial dapat meningkatkan rasa ingin tahu konsumen, sehingga dapat meningkatkan niat beli terhadap produk atau jasa yang ditawarkan. 25 Hal ini dapat dimanfaatkan bagi tim manajerial untuk menyusun strategi pemasaran lewat media sosial dalam mencapai target konsumen yang sesuai.…”
Section: Tabel 4 Collinearity Statistics (Inner Vif)unclassified
“…Jika dilihat dari hasil Tstatistics dan P value nya, dari total 9 hipotesis yang diuji, 4 diantaranya tidak menunjukkan hubungan yang signifikan dan tidak menunjukkan hasil yang sejalan dengan penelitian terdahulu. 19,20 Studi lainnya oleh Kaur et al (2021) menunjukkan adanya pengaruh yang positif dan signifikan dari epistemic value terhadap purchase intention, maka dapat disimpulkan bahwa dengan pemasaran produk di media sosial dapat meningkatkan rasa ingin tahu konsumen, sehingga dapat meningkatkan niat beli terhadap produk atau jasa yang ditawarkan. 25 Hal ini dapat dimanfaatkan bagi tim manajerial untuk menyusun strategi pemasaran lewat media sosial dalam mencapai target konsumen yang sesuai.…”
Section: Tabel 4 Collinearity Statistics (Inner Vif)unclassified
“…Religious identity and religiosity have been shown to stimulate consumers' product choice (Rahman et al, 2015). Religiosity has a positive and significant impact on perceived value (Auliarahman & Sumadi, 2020). Karsi (2013) showed that religiosity plays a significant role in the decision of charitable giving.…”
Section: Impact Of Religiosity On Perceived Compliance Of Islamic Mar...mentioning
confidence: 99%
“…The development of technology and digital intelligence that is becoming increasingly advanced can bring new opportunities for marketers to market products to increase consumers' purchase intentions (Auliarahman & Sumadi, 2020). However, it is undeniable that conditions during the COVID-19 pandemic significantly affected consumer behavior related to purchasing intentions for a product or service.…”
Section: Introductionmentioning
confidence: 99%
“…The use of social media platforms with live streaming features for shopping media is one of the trends in online shopping behavior during the COVID-19 pandemic. Video technology is believed to be able to match consumers' expectations to shop online while still being able to observe the diversity of items or services supplied by digital video, indicating that the public has a greater intent to purchase digitally promoted things online (Auliarahman & Sumadi, 2020; Y. I. Putri, Pradana, Utami, Nugraha, & Karnovi, 2021;Simbolon, Nurcholifa, & Safarina, 2022).…”
Section: Introductionmentioning
confidence: 99%